A DEK domain-containing protein GhDEK2D mediated Gossypium hirsutum enhanced resistance to Verticillium dahliae. (31st December 2022) - Zhou, Jinglong; Zhao, Lihong; Wu, Yajie; Zhang, Xiaojian; Cheng, Sheng; Wei, Feng; Zhang, Yalin; Zhu, Heqin; Zhou, Yi; Feng, Zili; Feng, Hongjie
ABSTRACT: DEK is associated with DNA replication and break repair, mRNA splicing, and transcriptional regulation, which had been studied in humans and mammals. The function of DEK in plants was poorly understood. In this study, GhDEK 2D was identified in Gossypium hirsutum by genome-wide and post-translational modifications. GhDEK2D had been phosphorylated, acetylated and ubiquitylated under Verticillium dahliae ( Vd ) challenge. The GhDEK2D -silenced cotton decreased resistance against Vd . In GhDEK2D -silenced cotton plants, the reactive oxygen species was activated, the callose, xylogen, hypersensitive reaction (HR) and expression levels of defense-related genes were reduced. Homozygous overexpressing-GhDEK2D transgenic Arabidopsis lines were more resistant to Verticillium wilt (Vw). We propose that GhDEK2D was a potential molecular target for improving resistance to Vw in cotton.